Soy biodiesel emissions have reduced inflammatory effects compared to diesel emissions in healthy and allergic mice. (19th September 2015) - Gavett, Stephen H.; Wood, Charles E.; Williams, Marc A.; Cyphert, Jaime M.; Boykin, Elizabeth H.; Daniels, Mary J.; Copeland, Lisa B.; King, Charly; Krantz, Todd Q.; Richards, Judy H.; Andrews, Debora L.; Jaskot, Richard H.; et al.
Abstract: Toxicity of exhaust from combustion of petroleum diesel (B0), soy-based biodiesel (B100), or a 20% biodiesel/80% petrodiesel mix (B20) was compared in healthy and house dust mite (HDM)-allergic mice. Fuel emissions were diluted to target fine particulate matter (PM2.5 ) concentrations of 50, 150, or 500 μg/m 3 . Studies in healthy mice showed greater levels of neutrophils and MIP-2 in bronchoalveolar lavage (BAL) fluid 2 h after a single 4-h exposure to B0 compared with mice exposed to B20 or B100. No consistent differences in BAL cells and biochemistry, or hematological parameters, were observed after 5 d or 4 weeks of exposure to any of the emissions. Air-exposed HDM-allergic mice had significantly increased responsiveness to methacholine aerosol challenge compared with non-allergic mice. Exposure to any of the emissions for 4 weeks did not further increase responsiveness in either non-allergic or HDM-allergic mice, and few parameters of allergic inflammation in BAL fluid were altered. Lung and nasal pathology were not significantly different among B0-, B20-, or B100-exposed groups. In HDM-allergic mice, exposure to B0, but not B20 or B100, significantly increased resting peribronchiolar lymph node cell proliferation and production of TH 2 cytokines (IL-4, IL-5, and IL-13) and IL-17 in comparison with air-exposed allergic mice. These results suggest that diesel exhaust at a relatively high concentration (500 μg/m 3 ) can induce inflammation acutely in healthy mice and exacerbate some components of allergic responses, while comparable concentrations of B20 or B100 soy biodiesel fuels did not elicit responses different from those caused by air exposure alone.